2018
DOI: 10.5812/intjssh.83782
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Dietary Intake Between Before, During and After Ramadan Observance in Tunisian Physically Active Men: A Systematic Review

Abstract: Objective: The present review was designed to systematize the literature on the evolution of dietary intake in Tunisian physically active subjects (i.e., physically active men and physical education students) between before, during and after Ramadan observance. Evidence Acquisition: Two electronic databases, PubMed and Science direct, were searched using a comprehensive strategy. Studies published prior to August 2018 were included if they assessed dietary intake during Ramadan in Tunisian physically active su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 38 publications
2
23
0
1
Order By: Relevance
“…Ramadan observance could cause cumulative deficits of food and water intake, but in the present study, intakes did not change significantly, in agreement with Aziz et al [36] and the findings of a recent systematic review [23]. Night-time sleep is often delayed, and its duration tends to be reduced because of the large amounts of food that are consumed late at night [37].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Ramadan observance could cause cumulative deficits of food and water intake, but in the present study, intakes did not change significantly, in agreement with Aziz et al [36] and the findings of a recent systematic review [23]. Night-time sleep is often delayed, and its duration tends to be reduced because of the large amounts of food that are consumed late at night [37].…”
Section: Discussionsupporting
confidence: 91%
“…A deterioration of mood state and loss of sleep could also contribute to a decrease in performance during Ramadan [22,23,24]. To date, studies evaluating the impact of Ramadan observance on the stress level of athletes are lacking, but such information would help coaches and trainers to devise tactics to combat stress and maintain a normal level of vigilance.…”
Section: Introductionmentioning
confidence: 99%
“…Another significant factor for dietary habits change was Ramadan, as many people change their dietary routine to enable Islamic fasting practices. 25 Nevertheless, studies focused on dietary intake during Ramadan concluded that Ramadan fasting has no impact on feelings, dietary intake, and short-term maximal performance. 25 , 26 Also, our study used a self-administered questionnaire; individuals ranked their eating habit as healthier since they shifted to home-cooked meals, regardless of the quality and quantity of food.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in eating schedules as well as other activities (i.e., late prayer ( Taraweeh )) have considerable effects on sleep [ 4 , 5 , 6 , 7 ] and food/fluid intakes [ 8 , 9 ]. Other changes may also be observed during this month [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%